RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - FEDORENKO, VOLODYMYR; BEHDAI, ANASTASIIA; YAREMENKO, VOLODYMYR; CHORNIY, OLEKSANDR; GOY, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Oral administration of medicinal products (MPs) remains the most convenient and preferred method of delivery, ensuring high patient compliance. However, limited absorption due to low solubility or permeability of active pharmaceutical ingredients (APIs) often leads to low bioavailability of such drugs. To solve this problem, it is common to use solid dispersion systems (SDS) to improve the solubility of the API. For example, one such API that requires increased solubility is rivaroxaban, a direct oral factor Xa anticoagulant. However, the use of TDSs to increase the solubility of this API requires reliable analytical methods to evaluate their effectiveness, in particular, to study the plasma coagulation kinetics. Therefore, the aim of the study was to develop an in vitro analytical methodology for studying the kinetics of plasma coagulation using a laser nephelometer, which would allow to assess the effect of different approaches to increasing the solubility of APIs, in particular, TDS, and their direct impact on the key indicator - coagulation. The methodology was developed based on the analysis of literature data on methods for testing antithrombotic drugs. It was found that the determination of activated partial thromboplastin time (APTT) is an effective tool for assessing the effect of rivaroxaban. To use this tool, an analytical method was developed using the NEPHELOstar laser nephelometer. It included the optimisation of the sample composition (plasma, APTT reagent, calcium chloride, API solution) and the development of instrument parameters (temperature, laser width, sensitivity, cycle time, etc.). As a result of the study, the values of the instrument setup parameters were determined: temperature 37°C, laser beam width 1.7 mm, sensitivity 70%, cycle time 13 s, etc. The developed method allows visualising the effect of different concentrations of rivaroxaban (5 μM, 10 μM, 15 μM) on the kinetics of plasma coagulation. It was confirmed that this method allows to determine the dependence of coagulation kinetics on the concentration of rivaroxaban. The developed in vitro analytical method using a laser nephelometer is an effective tool for studying the coagulation kinetics of blood plasma and assessing the effect of anticoagulants, in particular rivaroxaban. The technique can be used to evaluate the effectiveness of various methods of increasing the solubility of APIs by analysing the plasma coagulation kinetics.